Foreign direct investment into Africa and the role of taxation : a case study of Ghana and Rwanda,with a focus on the influence of taxation incentive policies and regulations currently in force - Cullen, Catherine Laurá-Jeán (Department of Finance and Tax, 2015)
Includes bibliographical references.